2022
DOI: 10.1371/journal.pone.0263568
|View full text |Cite
|
Sign up to set email alerts
|

Application of Health Belief Model for the assessment of COVID-19 preventive behavior and its determinants among students: A structural equation modeling analysis

Abstract: Background COVID-19 is a new pandemic that poses a threat to people globally. In Ethiopia, where classrooms are limited, students are at higher risk for COVID-19 unless they take consistent preventative actions. However, there is a lack of evidence in the study area regarding student compliance with COVID-19 preventive behavior (CPB) and its predictors. Objective This study aimed to assess CPB and its predictors among students based on the perspective of the Health Belief Model (HBM). Method and materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…A very small significance of susceptibility to the disease and the observed severity of the disease were obtained in an earlier study (Clark et al, 2020). Perceived barriers to preventive behavior were significant predictors of preventive behavior in other studies (Asmundson et al, 2001;Barakat & Kasemy, 2020;Karimy et al, 2021;Karl et al, 2021;Mahindarathne, 2021;Shahnazi et al, 2020;Shitu et al, 2022;Zewdie et al, 2022), as well as perceived benefits of preventive behavior (Barakat & Kasemy, 2020;Clark et al, 2020;Karimy et al, 2021;Karl et al, 2021;Mahindarathne, 2021;Vardavas et al, 2020;Zewdie et al, 2022). These results suggest that public information campaigns and the promotion of preventive health behavior in relation to COVID-19 should be designed to focus on clearly presenting the benefits that respondents derive from such behavior, as well as on reducing barriers to its implementation.…”
Section: Discussionmentioning
confidence: 76%
“…A very small significance of susceptibility to the disease and the observed severity of the disease were obtained in an earlier study (Clark et al, 2020). Perceived barriers to preventive behavior were significant predictors of preventive behavior in other studies (Asmundson et al, 2001;Barakat & Kasemy, 2020;Karimy et al, 2021;Karl et al, 2021;Mahindarathne, 2021;Shahnazi et al, 2020;Shitu et al, 2022;Zewdie et al, 2022), as well as perceived benefits of preventive behavior (Barakat & Kasemy, 2020;Clark et al, 2020;Karimy et al, 2021;Karl et al, 2021;Mahindarathne, 2021;Vardavas et al, 2020;Zewdie et al, 2022). These results suggest that public information campaigns and the promotion of preventive health behavior in relation to COVID-19 should be designed to focus on clearly presenting the benefits that respondents derive from such behavior, as well as on reducing barriers to its implementation.…”
Section: Discussionmentioning
confidence: 76%
“…In the study of Shitu et al perceived barriers and self-efficacy were suggested as significant predictors of students’ compliance with COVID-19 preventive behavior. 28 Perceived barrier refer to one’s belief in the tangible and psychological costs of the advised behavior. 29 As the authors acknowledged, the biggest barrier for functional exercise was the lack of time.…”
Section: Discussionmentioning
confidence: 99%
“… Dymecka et al (2021) believe that individuals with high SOC were better equipped to handle difficult situations, reducing their probability of developing stress. A cross-sectional study from Ethiopia used the health belief model to predict COVID-19 preventive behavior among adolescents and found that the model explained more than 40% of the COVID-19 preventive behavior ( Shitu et al., 2022 ). With this in mind, it is important to follow up on students who have developed stress and mental health problems during the pandemic to avoid negative consequences.…”
Section: Discussionmentioning
confidence: 99%